The Post Office at Prayer?: Auditing Risk and Practice : A Safeguarding Appraisal - Billenness, Clive Stephen (Journal of Anglican studies, 2024)
Multiple instances of safeguarding failures and criticisms of poor process and weak governance have afflicted the Church of England for many years, despite repeated assurances that "Lessons would be learned". An Independent Safeguarding Board has been formed and then abolished without being replaced. A report by Professor Alexis Jay, former Chair of Independent Inquiry into Child Sexual Abuse, recommending the creation of two independent charities to oversee Church safeguarding has been passed to a Response Group and is being resisted by various groups within the Church. This article examines issues of the management of safeguarding within the overall governance of the organisation, compares issues within the Church with those which have been exposed by the Post Office Horizon scandal and considers the potential role of the audit function to concern itself with safeguarding matters as part of its oversight of risk management and corporate governance.